2017
DOI: 10.1007/s10640-017-0128-5
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Regulation and Sustainable Competitiveness: Evaluating the Role of Firm-Level Green Investments in the Context of the Porter Hypothesis

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 42 publications
(27 reference statements)
2
32
0
Order By: Relevance
“…Ghisetti & Rennings (2014) come to the same conclusion by using MIP 2009 data as explanatory variables, but dependent variables from the MIP 2011. Investigating a water withdrawal regulation in Germany, Stoever & Weche (2018) find that the regulation in question does not affect firms' overall profitability, even though it increases investments in integrated (resource efficiency-improving) technologies. Different outcomes between 2 Triguero et al (2013) only distinguish between small and medium-sized firms.…”
Section: The Porter Hypothesis and Size-dependent Differences Regardimentioning
confidence: 98%
See 1 more Smart Citation
“…Ghisetti & Rennings (2014) come to the same conclusion by using MIP 2009 data as explanatory variables, but dependent variables from the MIP 2011. Investigating a water withdrawal regulation in Germany, Stoever & Weche (2018) find that the regulation in question does not affect firms' overall profitability, even though it increases investments in integrated (resource efficiency-improving) technologies. Different outcomes between 2 Triguero et al (2013) only distinguish between small and medium-sized firms.…”
Section: The Porter Hypothesis and Size-dependent Differences Regardimentioning
confidence: 98%
“…Originally, the Porter hypothesis was built-up on market-based instruments (Porter & van der Linde 1995, Ambec et al 2013. Stoever & Weche's (2018) and Rexhäuser & Rammer's (2014) study, however, indicate that the type of environmental innovation (i.e. resource efficiency-improving vs. others)…”
Section: The Porter Hypothesis and Size-dependent Differences Regardimentioning
confidence: 99%
“…The effect of environmental regulation on corporate innovation activities is closely related to the industry in which the firm is located. Previous studies have shown that the stimulating effect of mandatory environmental regulation on technological innovation in heavily polluting industries is significantly higher than that in lightly polluting industries (Huang & Liu, ; Stoever & Weche, ). Then, is there any industry difference in the impact of VER on technological innovation?…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Second, the difference in the effects of VER on technological innovation in heavily polluting industries and lightly polluting industries is examined. In fact, existing studies had shown that the stimulating effect of mandatory environmental regulation on technological innovation in heavily polluting industries was significantly higher than that in lightly polluting industries (Huang & Liu, ; Stoever & Weche, ). Therefore, it is of great significance to test whether this difference is also reflected in VER.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in environmental policies worldwide have affected not only natural living conditions but also economic, social, and political consequences [1][2][3]. In this context, environmental protection, social equity, and well-being have become priorities in ensuring the concept of sustainable development [4][5][6]. In this respect, business process management plays an essential role in generating value for every business process, especially environmental sustainability [7][8][9].…”
Section: Introductionmentioning
confidence: 99%